2012
DOI: 10.3998/ark.5550190.0013.619
|View full text |Cite
|
Sign up to set email alerts
|

First total synthesis of salvianolic acid C, tournefolic acid A, and tournefolal

Abstract: First total synthesis of the natural product salvianolic acid C, tournefolal and tournefolic acid A has been described. The key benzofuran skeletons are prepared via selective iodination and Sonogashira reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A flame-dried 100-mL two-necked test tube equipped with a Teflon-coated magnetic stirring bar and a rubber septum was charged with 3,4-dibenzyloxy-1-iodobenzene 35 (1.04 g, 2.53 mmol, 1.0 equiv) and anhydrous THF (13 mL). After the solution was cooled to -78 °C, the resulting mixture was treated with n-BuLi (1.59 M in n-hexane, 1.65 mL, 2.63 mmol, 1.0 equiv) and stirred at -78 °C for 5 min.…”
Section: -[34-di(benzyloxy)phenyl]-4455-tetramethyl-132dioxaborolane (23)mentioning
confidence: 99%
See 1 more Smart Citation
“…A flame-dried 100-mL two-necked test tube equipped with a Teflon-coated magnetic stirring bar and a rubber septum was charged with 3,4-dibenzyloxy-1-iodobenzene 35 (1.04 g, 2.53 mmol, 1.0 equiv) and anhydrous THF (13 mL). After the solution was cooled to -78 °C, the resulting mixture was treated with n-BuLi (1.59 M in n-hexane, 1.65 mL, 2.63 mmol, 1.0 equiv) and stirred at -78 °C for 5 min.…”
Section: -[34-di(benzyloxy)phenyl]-4455-tetramethyl-132dioxaborolane (23)mentioning
confidence: 99%
“…6h,25b R f = 0.52 (CH 2 Cl 2 /methanol = 3:1); mp >250 °C; IR (ATR, cm −1 ): 3269, 2927, 1682, 1416, 1366, 1255, 1230, 1168, 816; 1 H NMR (400 MHz, CD 3 OD): δ 7.14 (s, 1H), 6.89 (s, 1H), 6.84 (d, 1H, J = 7.8 Hz), 6.82 (d, 1H, J = 1.8 Hz), 6.79 (s, 1H), 6.71−6.65 (m, 2H), 6.54 (d, 1H, J = 1.8 Hz), 6.46 (dd, 1H, J = 8.2, 1.8 Hz), 4.56 (t, 2H, J = 7.0 Hz), 2.96 (t, 2H, J = 7.0 Hz); 1 H NMR (400 MHz, DMSO-d 6 /CD 3 OD (4:1)): δ 7.19 (s, 1H), 7.06 (s, 1H), 6.81 (d, 1H, J = 8.4 Hz), 6.77 (d, 1H, J = 2.0 Hz), 6.75 (s, 1H), 6.63 (dd, 1H, J = 7.6, 2.4 Hz), 6.62 (d, 1H, J = 7.8 Hz), 6.59 (d, 1H, J = 2.0 Hz), 6.43 (dd, 1H, J = 8.0, 2.0 Hz), 4.49 (t, 2H, J = 7.4 Hz), 2.87 (t, 2H, J = 7.4 Hz); 13 2-[3,4-Di(benzyloxy)phenyl]-4,4,5,5-tetramethyl-1,3,2-dioxaborolane (23). A flame-dried 100 mL two-necked test tube equipped with a Teflon-coated magnetic stirring bar and a rubber septum was charged with 3,4-dibenzyloxy-1-iodobenzene 35 (1.04 g, 2.53 mmol, 1.0 equiv) and anhydrous THF (13 mL). After the solution was cooled to −78 °C, the resulting mixture was treated with n-BuLi (1.59 M in n-hexane, 1.65 mL, 2.63 mmol, 1.0 equiv) and stirred at −78 °C for 5 min.…”
Section: -(4-(benzyloxy)-3-iodophenyl)-3-(4-(benzyloxy)phenyl)-1-(2-(...mentioning
confidence: 99%
“…SalCm05, therefore, shows an attractive binding affinity to JAK with the value of −12.2 kcal/mol. (4) In the case of SalCm06 (Tournefolic acid A), it is shown that shortening the long side chain of SalC can improve GI absorption, but the relative binding affinity becomes weaker [ 46 ]. The molecule of Tournefolic acid A is smaller than that of Przewalskinic acid A ( Figure 5 ), but because its benzofuran location is similar to that of SalC, it shows relatively good binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was extracted into EtOAc (3 × 18 mL), and the extracts were combined and washed sequentially with saturated aqueous NaHSO 3 (2 × 15 mL), water (2 × 15 mL), and then brine (15 mL). The organic layer was dried over Na 2 SO 4 , filtered, and concentrated to give an off-white solid, which was recrystallized from petroleum ether/EtOAc to afford compound 9 (1.49 g, 90%) as a white, crystalline solid: mp 140 °C, lit . mp 138–141 °C (dec); 1 H NMR (300 MHz, CDCl 3 ) δ 10.01 (1H, s), 7.51 (1H, J = 8.5 Hz, d), 7.41 (5H, s), 6.97 (1H, J = 8.5 Hz, d), 6.47 (1H, brs), 5.22 (2H, s); 13 C NMR (75 MHz, CDCl 3 ) δ 195.0, 149.9, 146.0, 135.0, 129.0, 129.0, 129.0, 128.0, 123.7, 111.4, 71.7; ESIMS m / z 355 [M + H] + ; HRESIMS m / z 354.9834 [M + H] + (calcd for C 14 H 12 IO 3 , 354.9831).…”
Section: Methodsmentioning
confidence: 99%